Study of Susceptibility of Pari Island Groundwater – To Surface Water Using Natural Isotopes and Hydrochemicals - Pujiindiyati, E. Ristin; Sidauruk, Paston; Satrio,; Rustam, Agustin (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2015)
The Pari Island with a total area of 40,32 ha is situated at the southern end of a chain of more than a hundred islands, commonly known as Seribu Islands, in Java Sea. Its topography is flat land and mainly consists of coral reefs such that fresh water supply for local people is very limited. The scarcity of fresh water to the local people is still worsen by the intrusion of sea water to the aquifer system. The objective of this study is to get a better understanding of mixing process between sea water and ground water and to trace the sources of salinity in shallow groundwater of Pari Island. The combinations of natural isotopes of 18O and 2H in water and hydrochemical (such as Na+, K+, Ca2+, Mg2+, Cl-, SO42- and HCO3-) content were used in this study. Results of hydrochemicals showed that almost all of the shallow groundwaters of Pari island had undergone mixing process with sea water. Mostly, they were classified as brackish water and gradually changed to saline water along the flowpath of the water. Only two groundwater samples were still characterized as fresh water type. Mixing ratios of seawater-groundwater water were estimated to be between 2% and 38%. Isotopic results of 18O and 2H revealed that slope of groundwater samples had decreased compared to local water meteoric line. Obviously, those distributions a long the mixing line of sea water – rain water, indicated that high salinity of groundwaters in Pari Island originated from encroachment of sea water. It implied that the salinity was caused by flushing of minerals into soil by direct precipitation could not be taken into consideration.